A Spatial Econometric Analysis of Regional Specialisation Patterns Across EU Regions - Claudia Stirböck (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
This paper conducts a spatial econometric analysis of the determinants of regional specialisation patterns. Spatial autocorrelation is present, but is mostly due to spatial error autocorrelation. Spatial interaction due to economic interdependencies is only evident for some few labour-intensive sectors. Hereby, sectoral specialisation of a region seems to be positively influenced by the one of surrounding regions. However, we cannot identify clear disadvantageous spatial interdependencies of specialisation in the periphery or increasing core-periphery tendencies.
Keywords: R12; C31; F15; F2; 330; Regional Specialisation; Exploratory Spatial Data Analysis; Spatial Econometrics; Internationale Arbeitsteilung; Regionale Arbeitsteilung; Schätzung; EU-Staaten